Media diversity as a guarantee to cultural diversity: the promotion of identities from an international law approach - Barreiro Carril, Beatriz (CIC. Cuadernos de Información y Comunicación, 2016)
This article deals with several international instruments which provide legal guarantees for media diversity, which is essential for the promotion of cultural diversity. Based on several articles of the Convention of cultural diversity, the General Comment of the Committee on Economic, Social and Cultural Rights No. 21 on the right to take part in cultural life, as well as the work of the UN Independent Expert on Cultural Rights, this article aims to identify legal tools for the establishing of measures promoting cultural diversity in the media. This article looks at the case study of Honduran Garifuna community radios. It emphasizes the importance of taking into account the economic aspects of cultural and communicational rights.
Keywords: Cultural Diversity; Media Diversity; Garifuna Identity; Human Rights; Freedom of Expression; Right to Communicate; Cultural Rights; Cultural Diversity Convention